Cryptocurrency as Object of Regulation by Public and Private Law - TSINDELIANI, Imeda; EGOROVA, Maria (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020, 2020)
The aim of this study is to establish the legal status quo of cryptocurrencies in the Russian Federation. The hypothesis presented by this study requires a profound reference to existing and proposed legislation as well as to the statements of a number of international, supranational and national regulatory bodies. This study uses qualitative research methods, and primarily consists of descriptive research. Doctrinal and comparative law research also lie at the very heart of this paper as they enable the author to identify, analyze and synthesize a number of foreign (incl. EU), and Russian laws. As a result, the emergence of new institutions and the modernization of existing ones, based on new technological breakthroughs, undoubtedly affect the already existing institutions that are under the influence of changes. Money, which is at the heart of finance, already loses its material forms of expression and regulating properties, alternative tools emerge in the economy that are ready to act as alternatives to this traditional institution. The alternative to money and monetary mechanisms will affect the basic instrument for regulating economic relations and the financial system of the state as a whole - a monopoly on the issue of currency. The nature of cryptocurrency, its features do not make it possible to attribute it entirely either to the means of payment, or to securities, or property. In the existing international community, cryptocurrency lacks a single focal point. Only a progressive view and modern legal regulation of cryptocurrency will create conditions for the development of legal and, most importantly, safe relations in the field of cryptocurrency.